1989
DOI: 10.2307/1510726
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabled and Nondisabled College Students' Use of Structure in Recall of Stories and Text

Abstract: This study compared LD and average college students' use of expository text structure and story grammar to recall social studies text passages. Students simultaneously read and listened to three passages with different structures: story grammar, comparison, and causation. Results were analyzed for structure use in immediate oral recall. No difference was found between the groups on the use of story grammar and comparison structure. However, the LD students scored significantly lower than their average peers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Lecture Di f ferences Both groups were found to produce a significantly greater number of T-units and subordinate clauses in their retellings of the comparison lecture content compared with the causation lecture. This finding supports the hypothesis that the comparison discourse structure is more facilitative of recall than the causation discourse structure (Bacon & Carpenter, 1989; Richgels, McGee, Lomax, & Sheard, 1987). These researchers have presented results that suggest that discourse structure use is developmental, with use of a comparison discourse structure preceding use of a causation discourse structure.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Lecture Di f ferences Both groups were found to produce a significantly greater number of T-units and subordinate clauses in their retellings of the comparison lecture content compared with the causation lecture. This finding supports the hypothesis that the comparison discourse structure is more facilitative of recall than the causation discourse structure (Bacon & Carpenter, 1989; Richgels, McGee, Lomax, & Sheard, 1987). These researchers have presented results that suggest that discourse structure use is developmental, with use of a comparison discourse structure preceding use of a causation discourse structure.…”
Section: Resultssupporting
confidence: 84%
“…Data preparation indicated that the following dependent variables were found to be skewed (i.e., skewness divided by standard error of skewness 2.00; Tabachnick & Fidell, 1989) for the comparison lecture: number of (Copmann & Griffith, 1994). Given the proposal that participants use discourse structure to recall passage content (Bacon & Carpenter, 1989;Meyer & Freedle, 1984), it is possible that the ability to recall lecture components in this study reflected to some degree the ability to use expository discourse structure. If this were the case, then our data would support Bacon and Carpenter's finding that college students with NL used expository discourse structure better than their participants with LD in verbal retellings of a causation passage.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations